Current-balancing strategy for multileg interleaved DC/DC converters of electric-vehicle chargers - Choi, Hye Won; Kim, Seok Min; Kim, Jinwoo; Cho, Younghoon; Lee, Kyo Beum (Journal of Power Electronics, 2021)
A current-balancing strategy for a multileg interleaved DC/DC converter with a reduced number of current sensors for electric-vehicle chargers is proposed in this paper. There are imbalances between the leg currents of multileg DC/DC converters, which are caused by the difference between the leg impedances and the driver delay. Each of the leg current sensors must achieve current balancing. However, the conventional strategy is burdensome due to its high cost and volume. To mitigate these issues, the proposed balancing strategy effectively balances leg currents using fewer current sensors than the number of legs. The proposed strategy was verified by various simulation and experimental results.
Keywords: Balancing strategy; Current balancing; Current sensors; High costs; Current-balancing strategy; Electric vehicle charger; Multileg interleaved converter; Reducing current ripple